HIV entry inhibitors - Esté, José (Henry Stewart Talks, 2011)
HIV life cycle, The HIV-1 genome, Synthesis of HIV-1 envelope glycoproteins, Targets for antiretroviral therapy, Mechanism of HIV-1 entry, HIV entry inhibition, HIV-1 binding inhibitors, HIV-1 coreceptor inhibitors, Viral composition of pure/mixed populations, CXCR4 antagonists, Drugs blocking gp120-CCR5 interaction, Maraviroc, MOTIVATE 1 and 2 clinical trials, Coreceptor tropism by treatment status, Resistance in the absence of coreceptors, HIV-1 fusion inhibitors, TORO trials, Predictors of virological response, The virus-inhibitory peptide (virip), New strategies to prevent HIV infection